Experimental complex flow patterns in the pump intake with a low water level. Issue 1 (1st September 2022) - Guo, M; Tang, X L; Li, X Q
Abstract: The present paper is an extension of the authors' previous work [1], and the goal is to analyze and reveal the complex flow patterns in the pump intake with a low water level (lower than the critical water level) through PIV Technology (Particle Image Velocimetry). The results show that: the lower the water level (a) the geometric scale of the free-surface vortices increases, which potentially leads to pulling more air into the pipe system and the pump units of the pump station; (b) the sidewall-attached vortices have a larger geometric scale; (c) more backwall- and floor-attached vortices are captured, and their geometric scale is large. In brief, the experimental data of the paper indicate that the free-surface, backwall-, and floor-attached vortices are the main characters of the pump intake with a low water level. In engineering, the vortex suppression/eliminating devices in the vicinity of these locations should be emphasized.